Plk1, a promising THERAPEUTIC target for prostate cancer treatment - Peng, Jia; Nouri, Mansoureh; Maasoumyhaghighi, Hamed; Liu, Jinghui; Liu, Xiaoqi (Serican Journal of Medicine, 2024)
Prostate cancer is the most commonly diagnosed cancer and a leading cause of cancer-related mortality among men in the United States. Androgen deprivation therapy (ADT) has long been the cornerstone of treatment for advanced prostate cancer. However, most patients eventually develop resistance, leading to progression into the lethal castration-resistant prostate cancer (CRPC) stage, which is associated with poor survival rates. While next-generation androgen receptor signaling inhibitors (ARSIs), such as enzalutamide and abiraterone, have revolutionized CRPC treatment, resistance to these therapies remains a significant challenge, rendering the disease incurable. Recent studies have identified Polo-like kinase 1 (PLK1), a master regulator of mitosis, as a key driver of prostate cancer progression, particularly in CRPC. PLK1 activation has been linked to critical pathways, including oxidative stress responses, lipid metabolism, and androgen receptor (AR) signaling, which collectively promote tumor growth and ARSIs resistance. Moreover, PLK1 can regulate chromosomal stability and DNA damage repair pathways, contributing to sensitivity to irradiation therapy. Additionally, PLK1 plays a role in driving resistance to targeted therapies, such as PARP inhibitors, in BRCA-mutant CRPC. Compelling evidence further suggests that combining PLK1 inhibition with paclitaxel could serve as an effective therapeutic strategy to overcome resistance in CRPC by targeting microtubule dynamics. This review examines the mechanistic role and broader implications of PLK1 in CRPC treatment, offering valuable insights into potential combination therapies to improve efficacy and patient outcomes.